Identification of Variants Responsible for Monogenic Forms of Diabetes in Brazil - Abreu, Gabriella de Medeiros; Tarantino, Roberta Magalhães; da Fonseca, Ana Carolina Proença; Andrade, Juliana Rosa Ferreira de Oliveira; de Souza, Ritiele Bastos; Soares, Camila de Almeida Pereira Dias; Cambraia, Amanda; Cabello, Pedro Hernan; Rodacki, Melanie; Zajdenverg, Lenita; Zembrzuski, Verônica Marques; Campos Junior, Mário (Frontiers in Endocrinology, 2022)
Monogenic forms of diabetes mellitus may affect a significant number of patients of this disease, and it is an important molecular cause to be investigated. However, studies of the genetic causes of monogenic diabetes, especially in populations with mixed ethnic backgrounds, such as the one in Brazil, are scarce. The aim of this study was to screen several genes associated with monogenic diabetes in fifty-seven Brazilian patients with recurrence of the disease in their families and thirty-four relatives. Inclusion criteria were: Age of onset ≤ 40 years old, BMI < 30 kg/m², at least two affected generations and negative anti-GAD and anti-IA2 antibodies. MODY genes HNF4A, GCK, HNF1A, HNF1B, NEUROD1, KLF11, PAX4, INS, KCNJ11, and MT-TL1 were sequenced by Sanger sequencing. We identified a total of 20 patients with variants, 13 GCK-MODY, four HNF1A-MODY, and one variant in each of the following genes, HNF4A, HNF1B and MT-TL1. Segregation analysis was performed in 13 families. Four variants were novel, two in GCK (p.(Met115Val) [c.343A>G] and p.(Asp365GlufsTer95) [c.1094_1095insGCGA]) and two in HNF1A (p.(Tyr163Ter) [c.489C>G] and p.(Val380CysfsTer39) [c.1136_1137insC]). Here we highlight the importance of screening for monogenic diabetes in admixed populations.